Artificial Intelligence Designated as Inventor – An Analysis of the Recent EPO Case Law. Issue 9 (3rd July 2020) - Stierle, Martin
Abstract: This paper will focus on the issue of designating artificial intelligence systems as inventors in the current framework of European patent law. Most recently, the European Patent Office rejected two patent applications which indicated a machine called DABUS as the inventor of the claimed subject-matter. The paper will analyse the grounds of the decisions in detail, thereby reflecting on the current approach of the European Patent Office to such designations and on the concept of inventorship within the European patent system in general.